Система общественных наук - Шаповал, Н. (Социология: теория, методы, маркетинг, 2001)
In the fragments taken from the "Social Science System and Sociography (Nationality Science)" book of M.Shapoval, the author substantiates his understanding of a social event by criticizing the ideas about society which existed at that time, in particular the organizational theory of society (very popular at that time). Regarding a social event as human inter-relations, M.Shapoval sets the following "logical categories of sociality" as prior: people, factors, activity and product.